Korelasi Antara Kecerdasan Emosional dengan Interaksi Sosial Siswa di Sekolah Dasar - Wahyuni, Sri; Kasriman, Kasriman (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research explains whether there is a relationship between students' emotional intelligence and social interaction in class V students. This research uses quantitative research with a descriptive approach and uses a questionnaire with a Likert scale type and has 5 alternative answers. At the start of the research, the questionnaire was tested by a team of experts (validators) to ensure that the questionnaire was suitable for use in research. Then the questionnaire sheet was tested on fifth grade students, then analyzed using validity and reliability tests. You can see whether the question items are valid or not, then analyzed for research using valid and reliable question items (validity test and reliability test). Then further research was carried out using data analysis tests using simple linear regression tests and hypothesis testing was carried out using the t test, f test and coefficient of determination. The results of the research can be concluded that the research data carried out is in accordance with the collection procedures carried out using the SPSS 22 program. This is proven by the results of data analysis tests using simple linear regression techniques so that the F_regression value = 15.352 > 4.14 with a significance of 0.000<0.05 is obtained. From these results, emotional intelligence has an effective contribution of 31.7% to social interaction. These data can be said to show that there is a relationship between emotional intelligence and social interaction.